APPLICATION OF THE MAUT METHOD IN RECIPIENTS INDONESIA SMART PROGRAM (PIP) IN 014673 MEKAR SARI ELEMENTARY SCHOOL - Sapriyanti, Sapriyanti; Risnawati, Risnawati; Saputra, Endra (STMIK Royal, 2024)
Abstract: Many children drop out or stop school due to economic constraints, especially personal costs such as not being able to buy school supplies, educational development donations and so on. Therefore, the government has a policy to help by issuing the Smart Indonesia Program (PIP) as a goal to help students' personal costs in pursuing education. As the smart Indonesia program progresses, many parents of students complain because the selection of students receiving PIP assistance is not on target and does not comply with the provisions. As with the data collection of students receiving the Smart Indonesia Program (PIP) assistance at State Elementary School 014673 Mekar Sari Village, it is also not optimal where the recording system is still inputted into Microsoft Excel. Therefore, a system is needed that is integrated with a calculation processing technique, namely a decision support system used at State Elementary School 015673 Mekar Sari Village to determine prospective recipients of the Smart Indonesia Program assistance who are truly worthy and appropriate. For this reason, this study uses the Multi-Attribute Utility Theory (MAUT) method to find students who are eligible for PIP benefits in the determination process.Keywords: maut method; mekar sari elementary school; smart indonesia program. Abstrak: Banyaknya anak yang putus atau berhenti sekolah dikarenakan kendala ekonomi terutama pada biaya pribadi seperti tidak mampu membeli perlengkapan sekolah, uang sumbangan pembinaan pendidikan dan lain sebagainya. Maka dari itu pemerintah memiliki kebijakan untuk membantu dengan mengeluarkan Program Indonesia Pintar (PIP) sebagai tujuan untuk membantu biaya pribadi siswa dalam menempuh pendidikan. Seiring berjalannya program indonesia pintar banyak kalangan orang tua siswa mengeluh dikarenakan dalam pemilihan siswa penerima bantuan PIP tidak tepat sasaran dan tidak sesuai dengan ketentuan. Seperti halnya dengan pendataan siswa penerima bantuan Program Indonesia Pintar (PIP) di Sekolah Dasar Negeri 014673 Desa Mekar Sari juga belum optimal dimana masih sistem pencatatan lalu di input ke Microsoft Excel. Maka dibutuhkan sebuah sistem yang sudah terintegrasi dengan sebuah teknik pengolahan perhitungan yaitu sistem pendukung keputusan yang digunakan pada Sekolah Dasar Negeri 015673 Desa Mekar Sari untuk penentuan calon penerima bantuan Program Indonesia Pintar yang benar layak dan pantas. Untuk itu penelitian ini menggunakan metode Multi-Attribute Utility Theory (MAUT) untuk mencari siswa yang layak mendapat manfaat PIP dalam proses penentuannya.Kata kunci: metode maut; program indonesia pintar; sd negeri mekar sari.